Ethics in Sambas Malay Regional Literary Texts - Effendy, Chairil; Muhammad, Asrori (Advances in Social Sciences Research Journal, 2024)
This research seeks to explore and understand the ethical values reflected in the texts of Sambas Malay folklore. Thirty-five (35) texts were studied, which are compiled in seven (7) books of Sambas Malay folk tales, namely Si Gentar Alam, Datuk Kulup, Anak Hantu, Kalantika, Si Miskin dan Firman Tuhan, Kandung Dagang Palembang, and Nek Kuntan. Through the close reading method, ethical values that guide the lives of the communities owning these texts were found. The dominant values relate to honesty, loyalty, a sense of shame, humility (not being arrogant), prioritizing others (altruism), forgiveness, religious devotion, caring for the poor, obedience to parents, respect for leaders, and respect for others. These ethical values have preserved the life of the community for centuries. In navigating life in an era filled with rapid change, high uncertainty, complex issues, and ambiguity resulting from technological disruption, these values remain highly relevant. Therefore, these ethical values need to continue being internalized in the lives of the Sambas Malay community in particular, and Indonesian society in general.